2005
DOI: 10.1029/2005ja011058
|View full text |Cite
|
Sign up to set email alerts
|

ULF geomagnetic pulsations in the southern polar cap: Simultaneous measurements near the cusp and the geomagnetic pole

Abstract: During November 2003, a 1‐week test campaign of ULF geomagnetic field measurements was conducted at the new Italian/French base of Concordia (Dome C, Antarctic plateau), close to the geomagnetic pole, at a corrected geomagnetic latitude of ∼89°S. An analysis of these measurements is presented, together with a comparison with simultaneous measurements conducted at the Italian “Mario Zucchelli” base, at Terra Nova Bay, also located in the polar cap, but at lower latitude (∼80°S). The variable solar wind and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…The most accepted mechanisms for the entry of upstream wave energy into the magnetosphere are basically two: a direct propagation through the subsolar region (Russell et al, 1983) and an indirect process involving particle and current modulation at the near-cusp ionosphere (Engebretson et al, 1991). Recently, in order to interpret some aspects of the Pc3 activity in the polar cap, Chugunova et al (2004Chugunova et al ( , 2006 proposed an additional propagation path of upstream waves to the ground via the magnetotail lobes (see also De Lauretis et al, 2005). In the magnetosphere, due to the latitudinal dependence of the field line length, upstream waves can couple to fundamental FLRs at low and mid latitudes, and to higher harmonics at high latitudes (Howard and Menk, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The most accepted mechanisms for the entry of upstream wave energy into the magnetosphere are basically two: a direct propagation through the subsolar region (Russell et al, 1983) and an indirect process involving particle and current modulation at the near-cusp ionosphere (Engebretson et al, 1991). Recently, in order to interpret some aspects of the Pc3 activity in the polar cap, Chugunova et al (2004Chugunova et al ( , 2006 proposed an additional propagation path of upstream waves to the ground via the magnetotail lobes (see also De Lauretis et al, 2005). In the magnetosphere, due to the latitudinal dependence of the field line length, upstream waves can couple to fundamental FLRs at low and mid latitudes, and to higher harmonics at high latitudes (Howard and Menk, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When corrected by means of our method, the azimuthal angle at TNB changes, becoming similar to the angle at TLD, while the polarization ratio and ellipticity do not change significantly. These results indicate that the azimuthal angle of polarized ULF waves at the coastal station of TNB is probably affected by horizontal ground conductivity anomalies, attributable to the sea saltwater, as suggested by De Lauretis et al (2005).…”
Section: Discussionmentioning
confidence: 60%
“…This example clearly shows that the polarization characteristics (more evident in the azimuthal angle in this case study) may be affected by ground conductivity anomalies, probably due to the closeness of TNB to the coastline, as suggested by De Lauretis et al (2005) and also observed by Regi et al (2017) in the higher Pc1-2 frequency range and evidenced by the interstation induction arrows at coastal stations.…”
Section: Vertical and Horizontal Transfer Functions Using The Interstmentioning
confidence: 94%
See 2 more Smart Citations